2011
DOI: 10.3109/09638288.2011.641664
|View full text |Cite
|
Sign up to set email alerts
|

Health, work, and personal-related predictors of time to return to work among employees with mental health problems

Abstract: Our results indicate that time to RTW is determined by both health- and work-related factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
2
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 23 publications
4
43
2
4
Order By: Relevance
“…Earlier studies have shown that mental disorders reduce the chance of RTW [10,[25][26][27]. Most studies on mental disorders focus on common mental disorders such as depression or mood disorders (F30-F39) and anxiety disorders (F40-F43) [10,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have shown that mental disorders reduce the chance of RTW [10,[25][26][27]. Most studies on mental disorders focus on common mental disorders such as depression or mood disorders (F30-F39) and anxiety disorders (F40-F43) [10,13].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have, in general, focused either on broad categories of diagnoses due to limited study size [6,8] or on more specific categories such as mental disorders or musculoskeletal diseases, which are the most common causes of prolonged sick leave [9][10][11][12][13][14][15]. Even though differences in recovery due to different diseases and disorders are supposedly common knowledge in the medical profession and clinical practice, no thorough description across different diagnoses as regards RTW is at hand.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated predictors of first SA and return to work (RTW) among workers with CMD (7)(8)(9)(10)(11), but limited evidence is available on factors predicting recurrent SA among such workers. Recent studies have shown that recurrent SA is a frequent problem among this worker population: 20-30% of workers who returned to work after SA due to a CMD experience a recurrence of sick leave (12,13).…”
mentioning
confidence: 99%
“…However, these two studies did not investigate other potential predictors. Several studies (7,8,10,11,(17)(18)(19) have identified predictors of first SA and RTW among workers with CMD, such as disease-related factors (eg, Predictors of recurrent sickness absence in common mental disorders severity of mental health problems, problem duration, SA) and work-related factors (eg, decision authority, skill discretion, work motivation). Nevertheless, research is needed that specifically focuses on predictors of recurrent SA as these could differ from predictors for first SA.…”
mentioning
confidence: 99%
“…They found that anxiety was common during the study time, and represents a risk of stagnation in professional development. Increased psychological distress is also associated with increased sick leave (Nielsen et al, 2012;Nystuen, Hagen, & Herrin, 2001). In a recent study, individuals working in the so-called "life professions" are more likely to be at risk for a disability pension in Norway (Tufte, 2013).…”
Section: Ethicsmentioning
confidence: 99%